Structural Equations of the Organizational Innovation Model with the Role of Intellectual Capital in Organizations - Khalif Al Saeidi, Mohamad Abdul Hasan; Bahrami, Hamid Reza; Shlaka , Tariq Kadhim; Aghaei, Enayat Ollah; Sadeghi, Mehrdad (Digital Transformation and Administration Innovation, 2025)
Undoubtedly, human capital constitutes the core pillar of every organization. On the other hand, innovation is indispensable for the survival of organizations. The present study analyzed the structural equations of the organizational innovation model, emphasizing the role of intellectual capital within organizations. Methodologically, the study employed a quantitative-descriptive approach based on structural equation modeling. Furthermore, the study is applied in nature. The statistical population comprised experts, managers, supervisors, and board members of the Ur Company in Iraq, totaling 195 individuals. Accordingly, the sample size was determined as 130 based on Cochran's formula. A researcher-made questionnaire was used as the data collection instrument. To evaluate the reliability of the instrument, Cronbach’s alpha method was applied, yielding an overall reliability coefficient of 0.93. For data analysis, structural equation modeling was conducted using Amos version 24. Based on the research findings, causal conditions had a significant effect on the core phenomenon. The standardized path coefficient (β) was 0.66. The standardized path coefficient for intervening factors on strategies was 0.26, indicating a positive and moderate relationship between contextual factors and strategies. The standardized path coefficient (β) for strategies was 0.32, reflecting a moderately positive relationship between strategies and outcomes. Ultimately, all model fit indices, including RMSEA and CFI, demonstrated acceptable results, indicating a good fit of the proposed model with the data. It can be concluded that innovation based on an intellectual capital approach—especially in large companies such as Ur Company in Iraq—can, through the utilization of appropriate organizational infrastructures, innovative strategies, and knowledge management, lead to enhanced performance and organizational credibility.